OPTIMAL RISK MEASURE FOR REINSURANCE MODEL - Claudya Christha, Dywa
the policyholders if they submit a very large claim. The higher risk that is given to reinsurance companies, the risk of insurance companies is getting smaller, but reinsurance premiums are getting bigger and vice versa. As a result, there is a point where the insured risk minimizes the potential losses that the insurance company will face. Choosing the right reinsurance model for insurance companies can reduce risk effectively. This Final Project determines the optimal reinsurance model by minimizing two risk measures, namely Value-At-Risk (VaR) and Tail-Value-at- Risk (TVaR) in the insurance company total cost model. The reinsurance model discussed are the proportional reinsurance model (Quota-Share), non-proportional (Stop-Loss) and combinational of proportional and non-proportional (Change- Loss) with premium calculation using the expectation premium principle. In this Final Project, the determination of retention and boundary (deductible) is optimally implemented in the data on the total claims of ABC health insurance products that follow the GEV distribution with parameters k = 0; 80799, = 4; 9171 105 and = 4; 0044 105 and the Weibull distribution with parameters = 0; 62375 and = 1; 5461 106.